(untitled) (Journal of Universal Science Research, 2024)
The territory of the Republic of Uzbekistan is a country rich in medicinal herbs. On the basis of medicinal plants, which are widely used in folk medicine and scientific medicine by scientists of our institute, a new plant collection has been developed, which is intended for use in cases of iron deficiency, and its 10% tincture drug form is conditionally called “Phytopheron”. The study of the effects of phytopheron on the central nervous system through its effects on the effects of sleeping and narcotic drugs.